Library of Congress catalog. Books: subjects; a cumulative list of works represented by Library of Congress printed cards
Beginning with 1953, entries for Motion pictures and filmstrips, Music and phonorecords form separate parts of the Library of Congress catalogue. Entries for Maps and atlases were issued separately 1953-1955.